Circ_0049447 acts as a tumor suppressor in gastric cancer through reducing proliferation, migration, invasion, and epithelial-mesenchymal transition. Issue 11 (5th June 2021) - Tang, Kai-Wen; Guo, Zhe-Xu; Wu, Zhong-Hua; Zhou, Cen; Sun, Jie; Wang, Xin; Song, Yong-Xi; Wang, Zhen-Ning
Abstract: Background: Although increasing abnormal expression of circular RNAs (circRNAs) has been revealed in various cancers, there were a small number of studies about circRNAs in gastric cancer (GC). Here, we explored the expression and function of a novel circRNA, circ_0049447, in GC. Methods: A total of 80 GC tissues and non-tumorous tissues were collected from the First Affiliated Hospital of China Medical University. And all cells were cultured with 10% fetal bovine serum and incubated at 37°C and 5% CO2 . The expression of circ_0049447 was quantified by real-time polymerase chain reaction. The biological function of circ_0049447 on proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) was evaluated by cell counting kit-8 (CCK-8), colony formation assay, transwell migration and invasion assay, and Western blotting. Luciferase report assay was used to verify the direct binding between circ_0049447 and predicted microRNA (miRNA). Furthermore, a xenograft mouse model was used to validate the function of circ_0049447 in vivo . Results: We demonstrated that circ_0049447 was downregulated in GC ( P  < 0.001). The area under the receiver operating characteristic curve reached 0.838, while sensitivity was 82.3% and specificity was 77.2%. CCK-8 and colony formation assay showed that overexpression of circ_0049447 could inhibit the proliferation ( P  < 0.05). Transwell migration and invasion assay showed upregulated circ_0049447 could impede migration in GC cells ( P  < 0.05). In addition, overexpression of circ_0049447 could impede GC cell EMT. Upregulation of miR-324-5p in GC specimens and direct binding between miR-324-5p with circ_0049447 proven by luciferase reporter assay indicated that circ_0049447 may inhibit GC by sponging certain miRNA. Conclusion: Circ_0049447 acts as a tumor suppressor in GC through reducing proliferation, migration, invasion, and EMT, and it is a promising biomarker for diagnosis.